A new genus and two new species of stoneflies (Plecoptera: Perlodidae) from Guizhou Province, China - Huo, Qing-Bo; Du, Yu-Zhou (Zootaxa, 2020)
A new genus of family Perlodidae, Parisoperla Huo & Du, gen. nov. is described including two new species from Guizhou Province in southwestern China. Both sexes of the new genus are characterized by the posterior margin of tergum 10 with a sclerotized process. The male membranous aedeagus is covered ventrally by patches of fine spines.